Study on emission and performance of diesel engine using castor biodiesel - Md. Saiful Islam,; Ahmed, Abu Saleh; Islam, Aminul; Abd. Aziz, Sidek; Low, Chyi Xian; Mridha, Moniruzzaman (Hindawi Publishing Corporation, 2014)
This paper presents the result of investigations carried out in studying the emission and performance of diesel engine using the castor biodiesel and its blend with diesel from 0% to 40% by volume. The acid-based catalyzed transesterification system was used to produce castor biodiesel and the highest yield of 82.5% was obtained under the optimized condition. The FTIR spectrum of castor biodiesel indicates the presence of C=O and C–O functional groups, which is due to the ester compound in biodiesel. The smoke emission test revealed that B40 (biodiesel blend with 40% biodiesel and 60% diesel) had the least black smoke compared to the conventional diesel. Diesel engine performance test indicated that the specific fuel consumption of biodiesel blend was increased sufficiently when the blending ratio was optimized. Thus, the reduction in exhaust emissions and reduction in brake-specific fuel consumption made the blends of caster seed oil (B20) a suitable alternative fuel for diesel and could help in controlling air pollution.